Case-based models of customer-perceived sustainable marketing and its effect on perceived customer equity - Sun, Y.; Garrett, T.; Phau, Ian; Zheng, B. (Elsevier, 2018)
This study presents case-based models that determine which sustainable marketing activities customer groups perceive to either enhance or reduce customer equity for a major sports clothing brand in China and South Korea. Complexity theory is used to identify different antecedents of customer equity that lead to the same outcomes. The study explores configurations of three dimensions of sustainable marketing that may affect customer equity. Young Chinese (n = 457) and Korean (n = 315) customers of a major sports clothing brand are surveyed to explore what configurations reduce or enhance the perception of customer equity and to test cultural differences. Academic and practical implications are also discussed.